2018
DOI: 10.1016/s2352-4642(18)30202-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental and sexual health outcomes following sexual assault in adolescents: a prospective cohort study

Abstract: National Institute for Health Research Policy Research Programme grant (115/0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 35 publications
3
76
0
4
Order By: Relevance
“…The analysis also showed that a history of sexual assault was associated with a 5‐fold and nearly 3‐fold increase in the odds of reporting depression among boys and girls in the sample, respectively. This is consistent with past research on traumatic stress 8,46‐49 . In the current sample, 1 in 10 students reported a history of sexual assault, with 70% of those being female students.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis also showed that a history of sexual assault was associated with a 5‐fold and nearly 3‐fold increase in the odds of reporting depression among boys and girls in the sample, respectively. This is consistent with past research on traumatic stress 8,46‐49 . In the current sample, 1 in 10 students reported a history of sexual assault, with 70% of those being female students.…”
Section: Discussionsupporting
confidence: 91%
“…The sample is from a prospective observational cohort study (Khadr et al, 2018) of adolescents who sought help, after a sexual assault, from any of the three Sexual Assault Referral Centres (SARCs) serving London. Adolescents aged 13-17 years attending during April 2013-2015 were invited to participate.…”
Section: Participantsmentioning
confidence: 99%
“…Most assaults involved vaginal, oral and/or anal rape (92%) and the assailant was a stranger in 37% of cases. More detailed information about the characteristics of the sample and ethical approval are reported elsewhere (Khadr et al, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…It is an experience than can levy a heavy toll upon an individual's mental health, (Frazier, Conlon, & Glaser, ) which may persists over time becoming chronic and enduring. Conversion to more severe mental illness has been reported (Khadr et al, ), the diagnosis of which can be stigmatizing leading to the person feeling devalued, rejected and isolated (Martinez, Piff, Mendoz‐Denton, & Hinshaw, ) whilst they continue to experience further sexual violence and assault (Khadr et al, ). It is also reported that admission to the supposed safety of a mental health ward only increases the risk of sexual violence and, that sexual incidents maybe well be commonplace on such wards (Care Quality Commission, ).…”
Section: Sexual Violence and Mental Healthmentioning
confidence: 99%